Factors Influencing the Consumption of Seafood in Istanbul, Turkey - EYGİ ERDOĞAN, BİRSEN (CENTRAL FISHERIES RESEARCH INST, 2011)
Scientific data on the attitudes and knowledge of Turkish people regarding seafood consumption is very limited. Therefore, consumption habits and preferences of Turkish people for seafoods were evaluated, based on the example of Istanbul, which is the most crowded and cosmopolitan city of Turkey. Only 15.53% (151) of the 972 participants stated they never consume seafoods but none of them considered seafoods unhealthy. Their main reason for not consuming is odor and taste. A significant proportion of the participants (84.47%) were well aware of the nutrition value of seafoods. Former negative experiences didn't decrease consumption frequency. The rate of seafood consumers and the consumption frequency increases proportional to the age of the consumers. Most of the respondents (34.84%) consume seafood once a week and they believe that they should consume seafoods more often. If seafoods were more available, many participants (44.10%) stated that they would consume seafoods. The top three preferred fish were fatty species, while the most favorite seafood was mussel. Octopus was the most unfavorable seafood, and most of the participants were not familiar with surimi. Respondents mostly (96.59%) preferred to consume fresh seafoods, and canning was the favorite (37.64%) processing technology.
Keywords: Seafood; survey; questionnaire; attitude; demand; habit; POLYUNSATURATED FATTY-ACIDS; FISH CONSUMPTION; HEALTH; KNOWLEDGE; PREFERENCES; ATTITUDES; BEHAVIOR; PATTERNS; MEAT